Radiofrequency in female external genital cosmetics and sexual function: a randomized clinical trial. Issue 11 (November 2016) - Lordêlo, Patrícia; Leal, Mariana; Brasil, Cristina; Santos, Juliana; Lima, Maria; Sartori, Marair
Abstract Introduction and hypothesis Female sexual behavior goes through cultural changes constantly, and recently, some women have shown the desire the ideal genitalia. In this study, we aimed to evaluate clinical responses to nonablative radiofrequency (RF) in terms of its cosmetic outcome in the female external genitalia and its effect on sexual function. Methods A single-masking randomized controlled trial was conducted in 43 women (29 sexually active) who were unsatisfied with the appearance of their external genitalia. The women were divided into an RF group (n  = 21, 14 sexually active) and a control group (n  = 22, 15 sexually active). Eight sessions of RF were performed once a week. Photographs (taken before the first session and 8 days after the last session) were evaluated by the women and three blinded health professionals by using two 3-point Likert scales (unsatisfied, unchanged, and satisfied; and worst, unchanged, and improved). Sexual function was evaluated using the Female Sexual Function Index (FSFI) and analyzed using the Studentt test. Women's satisfaction and health professional evaluation were analyzed using the chi-square test and inter- and intragroup binomial comparisons. Results Satisfaction response rates were 76 and 27 % for the RF and control groups, respectively (p  = 0.001). All professionals found a clinical improvement association in the treated group with RF in comparison with the control group (p  < 0.01). The overall FSFI sexual function score increased by 3.51 points in the RF group vs 0.1 points in the control group (p  = 0.003). Conclusions RF is an alternative for attaining a cosmetic outcome for the female external genitalia, with positives changes in patients' satisfaction and FSFI scores.